Balancing valued tradition with innovation : when your product is a beloved classic, how do you update it to attract new customers? - Cancellieri, Giulia; Ferriani, Simone; Cattani, Gino (MIT Sloan Management Review, 2023)
Companies with a strong legacy and established brand face the quandary of maintaining their loyal customer base while appealing to an evolving market. An empirical study of audience responses to operas that have been reinterpreted to appeal to modern tastes provides lesson for how to leverage a historically strong brand to reach new customers, without alienating loyal fans.